2016
DOI: 10.5966/sctm.2016-0133
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expansion and Sustained Inductive Function of Skin-Derived Precursor Cells in Computer-Controlled Stirred Suspension Bioreactors

Abstract: Endogenous dermal stem cells (DSCs) reside in the adult hair follicle mesenchyme and can be isolated and grown in vitro as self‐renewing colonies called skin‐derived precursors (SKPs). Following transplantation into skin, SKPs can generate new dermis and reconstitute the dermal papilla and connective tissue sheath, suggesting they could have important therapeutic value for the treatment of skin disease (alopecia) or injury. Controlled cell culture processes must be developed to efficiently and safely generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Apart from cells of the “bulge,” stem cells reside specifically in the HF mesenchyme and function to replenish the dermal papilla and connective tissue sheath. They are called self-renewing dermal stem cells (DSCs) [ 56 , 57 ]. When transplanted, DSCs integrate with mesenchymal cells and they act together with epithelial stem cells, participating in creating new hair follicles [ 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from cells of the “bulge,” stem cells reside specifically in the HF mesenchyme and function to replenish the dermal papilla and connective tissue sheath. They are called self-renewing dermal stem cells (DSCs) [ 56 , 57 ]. When transplanted, DSCs integrate with mesenchymal cells and they act together with epithelial stem cells, participating in creating new hair follicles [ 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are called self-renewing dermal stem cells (DSCs) [ 56 , 57 ]. When transplanted, DSCs integrate with mesenchymal cells and they act together with epithelial stem cells, participating in creating new hair follicles [ 56 , 57 ]. In cultures, they form spherical, self-regenerating colonies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies have suggested that Sox2 is necessary for hair follicle induction, a more recent conditional knockout study has shown that Sox2 is not essential for HF morphogenesis . When adult Sox2 + hfDSCs are isolated and grown in vitro, we observe a rapid loss of Sox2 expression over time, yet retain at least partial inductive function which is sustained for several passages. Is Sox2 an intrinsic property of hfDSCs or is it environmentally regulated?…”
Section: Hfdscs Contribute To Functional Heterogeneity Within the Dpmentioning
confidence: 61%
“…However, a new way to expand SKP was highlighted in a recent scientific publication. Indeed, the expansion of SKPs can be enhanced using computer‐controlled stirred suspension bioreactors . This technique allows a large number of SKPs (five‐fold greater than static culture) to be cultivated from the same donor for clinical use.…”
Section: Potential Use Of Skps In Regenerative Medicinementioning
confidence: 99%